Jardins turcs des bords de la Seine normande - François Calame; François Texier (In Situ)
The Seine valley, at Rouen, is the site of many spontaneous workers’ gardens, occupying the so-called abandoned plots of land owned by the Rouen port authority. Most of the gardeners are Turkish and occupy the allotments as family units. From the outset they made a considerable effort to clear the land and, since the 1980s, they have been cultivating a variety of plants which bear witness to their Anatolian origins. Most of the plants grown are intended to end up as food, and cooking, sometimes done in the gardens themselves during the summer months, allows for a reinforcement of the strong cultural links around the family, family networks and the memory of the villages from which these people come. Makeshift architectural structures, often built out of recuperated materials, have been erected in the different cultivated gardens and offer shelter for the families and the festive reunions. Some remarkable trees, such as Japanese medlars or walnut trees, are scattered throughout the gardens which, today, deserve some form of recognition and protection as heritage.